Otitis media among elderly: incidence, complication and prevention - Al-Sadeeq, Hanadi; Algarni, Zafer; Alobaid, Abdullah; Aloyaid, Abdullah; Alotaibi, Mohammad; Al-Qwizani, Abdulmalek; Al-Baqami, Abdulmohsen; AlOmar, Zaid; Alsohabi, Hanan; Albather, Shima (International Journal Of Community Medicine And Public Health, 2018)
Though often considered a disease of children, otitis media can affect the elderly. The incidence of otitis media among elderly population is variable among countries, but generally low, with a value ranging from 0.25-9%. However, dangerous complications may occur. Otitis media is a complex spectrum of diseases that include acute otitis media, otitis media with effusion, suppurative otitis media, and mastoiditis. Otitis media in elderly doesn’t feature the classical presentation in children. Elderly patients experience otalgia with or without hearing loss or signs of inflammation. Infection may spread to either to adjacent structures leading to mastoiditis, petrositis, labyrinthitis, or facial nerve palsy, or intracranially leading to meningitis, subarachnoid abscess, subdural abscess, encephalitis, brain abscess, lateral or sigmoid venous sinus thrombosis, and otitis hydrocephalus. The mainstay strategies for prevention of otitis media are the adequate proper treatment of each infection, and tight control of modifiable risk factors such as tobacco smoking, immunosuppression, upper respiratory tract infection, allergy, and craniofacial abnormalities. Antimicrobial treatment should be continued for at least 10-14 years.